Desenvolvimento do método de extração por eletromembrana para análise de ácidos naftênicos em água produzida por espectrometria de massas de ultra-alta resolução - Araújo, Giovanna Lopes de (2021)
Miniaturized techniques are better alternatives than traditional sample preparation techniques. They use simpler and more direct approaches, reducing the waste generated at the end of the process. Innovatively, these techniques can be applied to create more eco-friendly routine methodologies that contribute to analytical chemistry. This work develops a methodology using Electromembrane Extraction (EME) for the extraction of carboxylic acids, called Naphthenic Acids (NAs). These toxic species are found in Produced Water (PW), an effluent from the petroleum industry. Comparing it to other miniaturized techniques, it obtains better recoveries and shorter extraction times with EME, due to the application of the electric field. The applicability of the EME technique is explored here for the first time in a matrix such as PW. For this, an adaptation of the traditional methodology was carried out, using the hollow fiber membrane in a “U” shape. The conditions that demonstrated the best performance for EME-UHRMS was the 1-decanol as an organic solvent in SLM, pH of 10, five minutes of extraction applying 200 V, and a ratio of 1:4 of matrix and buffer. A migration analysis of some analytes through the membrane was also performed, observing relationships between the Log P and ion mobility. The analytical performance of EME-UHRMS was evaluated for three standards of NAs, obtaining calibration curves with R2> 0.98. LODs and LOQs were between 0.12 to 0.20 μg mL-1 and 0.40 and 0.67 μg mL-1, respectively, generating a huge influence on the matrix of the research data. The relative recovery of the technique is 75% and 111%, adequate values for the EME methodology used. Finally, EME-UHRMS was effectively applied in the produced water sample, demonstrating a more homogeneous extraction of the analytes when compared to the ones obtained by the classical Liquid-Liquid Extraction (LLE) technique.